Single introductions of soil biota and plants generate long‐term legacies in soil and plant community assembly - Wubs, E. R. Jasper; Putten, Wim H.; Mortimer, Simon R.; Korthals, Gerard W.; Duyts, Henk; Wagenaar, Roel; Bezemer, T. Martijn; Suding, Katharine (Ecology letters, 2019)
Recent demonstrations of the role of plant–soil biota interactions have challenged the conventional view that vegetation changes are mainly driven by changing abiotic conditions. However, while this concept has been validated under natural conditions, our understanding of the long‐term consequences of plant–soil interactions for above‐belowground community assembly is restricted to mathematical and conceptual model projections. Here, we demonstrate experimentally that one‐time additions of soil biota and plant seeds alter soil‐borne nematode and plant community composition in semi‐natural grassland for 20 years. Over time, aboveground and belowground community composition became increasingly correlated, suggesting an increasing connectedness of soil biota and plants. We conclude that the initial composition of not only plant communities, but also soil communities has a long‐lasting impact on the trajectory of community assembly.